The most common injuries in the sport fishermen and the treatment of natural and traditional Medicine - Lina Belkis Gómez Santana; Silvio Rivera Espinosa; Martha Belkis Granado Gómez; Orlando Pedro Suárez Pérez (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2017)
Sport fishing is a risky activity. This research meets the goal of identifying the most common injuries in Cuban fishermen who participated in sport tournaments and its treatment with Natural and traditional Medicine (Green Medicine). It was carried out a descriptive observation and a survey applied to 150 participants, the sample was represented by 95 fishermen who suffered any kind of injury or accident in the national sport contests of the Cuban Federation of Sport Fishing. The scientific methods proved the evaluation and the motivation of research. This study reveals that most of the injured fishermen were affected in the muscle skeleton system (54,7 %) and skin (43, 1 %). It was also confirmed that the green medicine prevents serious health disorders.